SYTUACJA PRAWNA NASCITURUSA W ART. 9 PROJEKTU KODEKSU CYWILNEGO - Sokołowski, Tomasz (Wydział Prawa i Administracji UAM, 2009)
The paper discusses the main assumptions of article 9 of the new draft of the civil code which provides for the application of the paremia Nasciturus pro iam nato in the area of modern civil law. The deliberations include several issues pertaining to the legal position of an unborn child and, in particular, the absence of legal capacity or special capacity of the father that would allow him to declare paternity of the unborn child. The author identifies different regulations existing in administrative law, and especially in the law of health care. The paper concludes with a statement that new article 9 ascertains a better system of protection of the interests of an unborn child, even if it does not grant it any legal capacity.
LEGAL POSITION OF AN UNBORN CHILD UNDER ARTICLE 9 OF THE DRAFT OF THE NEW CIVIL CODE